Cultured : how traditional foods feed our microbiome - Courage, Katherine Harmon (Avery, an imprint of Penguin Random House, 2019)
In this engaging and eye-opening book, science journalist Katherine Harmon Courage investigates these questions, presenting a deep dive into the ancient food traditions and the latest research for maintaining a healthy gut. Courage<U+2019>s insights include: <U+2022> Meet your microbiome: What it is, how it works, and why it's essential for our immune system--and overall health <U+2022> Gut-friendly food traditions: A guided tour of artisanal makers of yogurt, kimchi, kefir, kombucha, olives, cocoa, and other vibrant, ancient foods from around the world that feed our microbiome (along with simple recipes for curious at-home cooks) <U+2022> Cutting-edge science: A first-hand look at some of the top lab facilities where microbiologists are working to better understand the human gut and how to feed it for good health.